Demystifying opioid conversion calculations : a guide for effective dosing - McPherson, Mary Lynn M. (American Society of Health-System Pharmacists, 2018)
Praised by practitioners, students and instructors for its engaging approach to teaching a very complex subject, Demystifying Opioid Conversion Calculations: A Guide for Effective Dosing, has long been the go-to guide for learning how to calculate opioid conversions. Now in its second edition, this reference is a must-have for clinicians involved in pain management at all levels. Written by pain management expert Mary Lynn McPherson, PharmD, MA, MDE, BCPS, CPE, Demystifying Opioid Conversion Calculations focuses on the calculations that practitioners use in actual practice, providing realistic.